2014
DOI: 10.1016/j.soilbio.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Elemental stoichiometry of Fungi and Bacteria strains from grassland leaf litter

Abstract: a b s t r a c tIn most terrestrial environments, our knowledge of the elemental composition and stoichiometry of microorganisms stems from indirect whole community analyses. In contrast, we have little direct knowledge of the elemental composition of specific microorganisms and the variation between and within Fungi and Bacteria. To address this issue, we isolated and identified the elemental content of 87 strains of Fungi and Bacteria isolated from grassland leaf litter. The isolated strains were affiliated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
110
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(129 citation statements)
references
References 42 publications
9
110
3
1
Order By: Relevance
“…Griffiths et al (2012) and Chen et al (2014) showed that different P fertilization regimes did not modify the C : N : P ratio of soil microorganisms in the long term on a grazed pasture, while they strongly modified the microbial P and C concentrations and the soil microbial community composition. Finally, Mouginot et al (2014) showed that the N : P ratios of fungi and bacteria isolated from grassland leaf litter were similar, whereas the C : N and C : P ratios were higher in fungi than in bacteria, which is in line with observations of higher P concentrations in bacteria than in fungi made by Bünemann et al (2008aBünemann et al ( , 2011.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Griffiths et al (2012) and Chen et al (2014) showed that different P fertilization regimes did not modify the C : N : P ratio of soil microorganisms in the long term on a grazed pasture, while they strongly modified the microbial P and C concentrations and the soil microbial community composition. Finally, Mouginot et al (2014) showed that the N : P ratios of fungi and bacteria isolated from grassland leaf litter were similar, whereas the C : N and C : P ratios were higher in fungi than in bacteria, which is in line with observations of higher P concentrations in bacteria than in fungi made by Bünemann et al (2008aBünemann et al ( , 2011.…”
Section: Introductionsupporting
confidence: 88%
“…This suggests that only extreme treatments (no fertilization in the past 30 years in the DOK or massive fertilizer inputs in Saria) can significantly affect microbial nutrient ratios. The number of soils studied here is too limited for a full statistical assessment, but the soil properties that seem to control organic matter and P accumulation are the type and content of clay minerals and oxides, soil structural stability (Frossard et al, 2000;Six et al, 2006), and the soil microbial community (Mouginot et al, 2014).…”
Section: Importance Of Inputs Versus Soil Properties In Determining Smentioning
confidence: 99%
“…One source is organic N bound in plant tissues and microorganisms. Because the average C/N ratio is much higher in plant litter than in microbial decomposers, N availability is thought to limit litter decomposition (4)(5)(6). Fungal hyphae can further translocate N from the soil into plant litter (7).…”
mentioning
confidence: 99%
“…The C/N ratios BCN i are set to 4.59 and 8.30 for SOM and FOM specialists, respectively (Mouginot et al, 2014), based on the assumption that SOM decomposers are mainly bacteria and FOM decomposers are mainly fungi (Kaiser et al, 2014). …”
Section: Microbial Functional Typesmentioning
confidence: 99%